Couples’ Experiences of Vulnerability when Participating in the Reflecting Team Process: A Case Study - Egeli, Natasha Ann; Brar, Novjyot; Larsen, Denise J.; Yohani, Sophie (Canadian Journal of Counselling and Psychotherapy, 2014)
Clients’ experiences of vulnerability are anticipated to be a normal aspect of couple therapy where people expose personal and relational difficulties to others. However, no research has been conducted exploring clients’ experiences of vulnerability during this process. This qualitative case study attends to this gap in the literature. Researchers conducted interpersonal process recall interviews with three couples participating in the reflecting team (RT) process as part of their therapy. Results confirm that clients experience vulnerability in relation to a number of processes that occur during couple therapy and the RT process. Study limitations and future research recommendations are presented.